2016
DOI: 10.1158/1078-0432.ccr-15-2640
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tumor-Specific Agent for Intraoperative Near-Infrared Fluorescence Imaging: A Translational Study in Healthy Volunteers and Patients with Ovarian Cancer

Abstract: Purpose: Completeness of cytoreductive surgery is a key prognostic factor for survival in patients with ovarian cancer. The ability to differentiate clearly between malignant and healthy tissue is essential for achieving complete cytoreduction. Using current approaches, this differentiation is often difficult and can lead to incomplete tumor removal. Near-infrared fluorescence imaging has the potential to improve the detection of malignant tissue during surgery, significantly improving outcome. Here, we report… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
238
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 227 publications
(242 citation statements)
references
References 36 publications
3
238
1
Order By: Relevance
“…The disk can hold eight clear polypropylene tubes of 0.65 ml (Catalog # 15160, Sorenson, [3]) were used to make dilution series in Intralipid 2 %. All dilution series consisted of 21 concentrations, starting at 10,000 nM and, following one on one dilution with Intralipid 2 %, ending at 10 pM.…”
Section: Imaging System Performancementioning
confidence: 99%
See 2 more Smart Citations
“…The disk can hold eight clear polypropylene tubes of 0.65 ml (Catalog # 15160, Sorenson, [3]) were used to make dilution series in Intralipid 2 %. All dilution series consisted of 21 concentrations, starting at 10,000 nM and, following one on one dilution with Intralipid 2 %, ending at 10 pM.…”
Section: Imaging System Performancementioning
confidence: 99%
“…Fluorescence imaging (FI) is ideal for intraoperative applications due to fast acquisition times (milliseconds), flexibility in application, and portability [2]. Various tumor-targeted near-infrared (NIR) fluorescence agents have been successfully studied in clinical trials [3][4][5][6]. Moreover, there is great potential for a broad range of clinical applications besides oncology, such as infectious and inflammatory diseases [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In PDA, molecular imaging might enhance disease staging by enabling visualization of small PDA lesions, possibly leading to optimized selection of patients who will benefit from curative surgery. Clinical trials already demonstrated the feasibility of molecular fluorescence imaging in identifying micrometastases in peritoneal metastasized ovarian and colon cancer patients by targeting the folate a-receptor and vascular endothelial growth factor A (24)(25)(26). Besides, molecular imaging can be used to better assess the extent of the primary tumor during PDA surgery and evaluate essential resection planes.…”
Section: Discussionmentioning
confidence: 99%
“…OTL38 exploits highly specific FRα-targeted binding which has similarly observed with the visual contrast agent, EC17 (folate-FITC) [5]. Unlike EC17, folate is linked to a NIR fluorophore in OTL38 and emits in the NIR range (λ ex 774 and λ em 795) [6]. NIR imaging probes have several advantages over visual range probes; most notably, less autofluorescence and superior depth of penetration.…”
Section: Discussionmentioning
confidence: 99%